2011
DOI: 10.1111/j.1463-1318.2010.02528.x
|View full text |Cite
|
Sign up to set email alerts
|

Intersphincteric resection for low rectal cancer: laparoscopic vs open surgery approach

Abstract: Intersphincteric resection did not alter long-term tumour control of low rectal cancer. The safety and efficacy of the laparoscopic approach for intersphincteric resection are suggested by a similar short- and long-term outcome as obtained by open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 31 publications
8
52
1
Order By: Relevance
“…Most of the included studies defined conversion as any case that could not be completed with the intended minimally invasive surgical approach and required open or nonminimally invasive techniques for completion, [34][35][36]39,41,[43][44][45] and conversion patients remained in the LS group. Rates of conversion varied from 0 % in the study by Jun Seok 37 to 21.8 % in the study by Laurent, 43 while they were not reported in three studies.…”
Section: Study Characteristics and Qualitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the included studies defined conversion as any case that could not be completed with the intended minimally invasive surgical approach and required open or nonminimally invasive techniques for completion, [34][35][36]39,41,[43][44][45] and conversion patients remained in the LS group. Rates of conversion varied from 0 % in the study by Jun Seok 37 to 21.8 % in the study by Laurent, 43 while they were not reported in three studies.…”
Section: Study Characteristics and Qualitiesmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33] Thirteen articles were published in English for the final metaanalysis. [34][35][36][37][38][39][40][41][42][43][44][45] Among the involved articles, two of them were conducted from the same trial population, but offered difference indexes for analysis. Martijn 38 and Bonjer 46 included some patients with upper rectal cancer (DAV>10 cm), but we only analysed the data regarding the patients with mid-low rectal cancer (DAV≤10 cm).…”
Section: Studies Selectedmentioning
confidence: 99%
“…Thus, we believe in the potential of laparoscopic surgery for the LAP-ISR procedure. However, the evidence about LAP-ISR is still limited [4,5,18]. Therefore, the purpose of this study was to evaluate the efficacy of LAP-ISR in terms of mortality, morbidity, oncological adequacy, and functional results.…”
Section: Discussionmentioning
confidence: 99%
“…Laurent et al [5] reported the complications of LAP-ISR (n = 110) in a retrospective comparative study with their open ISR. In their report, overall morbidity was 40.9%, including 25.5% with septic pelvic complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation